PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Saputri, Marlinda; Setiawati, Setiawati; Sofyan, Deviana (Komunitas Manajemen Kompetitif, 2024)
The purpose of this study was to determine the effect of cash turnover and receivables turnover on profitability in transportation companies listed on the Indonesia Stock Exchange in 2020-2022. The population in this study were all transportation companies listed on the Indonesia Stock Exchange for the 2020-2022 period, namely 46 companies. From the criteria, the companies that met the requirements in this study were 13 transportation companies so that the total sample during the 2020-2022 period was 39 samples. The data collection technique used in this study was the documentation technique which was carried out in the form of annual report data from transportation companies listed on the IDX for the 2020-2022 period. The data analysis used was multiple linear regression analysis. The results of the study showed that partially cash turnover did not affect profitability in transportation companies listed on the IDX in 2020-2022, while receivables turnover affected profitability in transportation companies listed on the IDX in 2020-2022. 3. Simultaneously, cash turnover and accounts receivable turnover affect profitability in transportation companies listed on the IDX in 2020 - 2022.